Smart homes and health telematics, designing a better future : urban assisted living : 16th International Conference, ICOST 2018, Singapore, Singapore, July 10-12, 2018, Proceedings /: urban assisted living : 16th International Conference, ICOST 2018, Singapore, Singapore, July 10-12, 2018, Proceedings. (2018) - Unknown
No abstract available